Spiritual Assessment: What is your Method? - Linda L. Dunn (Rural Nurse Organization; Binghamton University, 2012)
In the last four issues of OJRNHC, varying aspects of spirituality have been addressed.  The focus moved across a continuum from one's personal responsibility to a professional responsibility.   Nurses in practice are mandated by accrediting bodies, such as Joint Commission on the Accreditation Healthcare Organizations (JCAHO)  , as well as professional codes, like the American Nurses  Association Code of Ethics, to ensure that every patient has a spiritual assessment.  In this editorial I would like to challenge every nurse to consider his/her own nursing practice and seriously ask yourself "how do I assess the spiritual needs of my patients?" Healthcare providers should have in place a tool by which all patients are spiritually assessed. Spiritual assessment is similar to the  nursing process in that  it is a process that begins when the patient is admitted and continues throughout his/her care.  Once the spiritual assessment screen has been completed, the spiritual care plan is then developed (Rumbold, 2007).  Many spiritual assessments are readily available; however, there is a JCAHO template useful to anyone desiring to create their own tool (Hodge, 2006).  In the college where I teach, the Faculty has just adopted the FICA spiritual assessment tool (Copyright, Christine M. Puchalski, MD, 1996) that the faculty will use in teaching spiritual assessment to our nursing students.  The FICA is an acronym for Faith and Belief, Importance, Community, and Address in Care.  I would suggest you consider using this tool in your nursing program or in your clinical practice.  Remember, the FICA is a guide, not a check-list to be completed.   You may access more information regarding the FICA by going to http://www.gwumc.edu. At this site, locate the search box and type in "FICA tool"; you will see may articles listed that will provide you with valuable information.  Also, go to http://www.gwish.org  - at this site, go to right lower web page and you will see  "Spiritual Assessment in Clinical Practice";  within this section click on "our new multimedia guide", then click on the picture of Dr. Puchalski.  You will find an abundance of information on spiritual assessment, particularly on the FICA.